Answer:
y = -3/2x +11
Explanation:
First you have to change the equation from standard form to slope form.
y = mx + b
2x-3y=7 --> subtract 2x from both sides
-3y = -2x + 7 --> now divide both sides by -3 to get y by itself
y = 2/3x - 7/3 --> the reason 2/3x is positive is because when there are two negatives it turns to a positive.
now you have to use point slope form y - y1 = m (x - x1)
x1 and y1 would be your point. 2 is x1 and 8 is y1
y - 8 = -3/2 (x - 2) --> the reason that m is -3/2 is because a perpendicular equation is the opposite reciprocal of the original slope
next distribute the -3/2
y-8 = -3/2x + 3 --> and now add 8 to 3 to get why by it self
now you have y = -3/2x + 11